(untitled) (Periphērica, 2024)
Poetics are the ancestral reparation, an ancient redress for all the destruction our technologies of power have created. The politics of literature today must experiment with the position of enunciation, affirming a position-in-the-world while radically avoiding the risk of reducing that creative position to a label, to a superficial gesture, to a stable “identity.” Political Literature today remakes the position of literature in the world (the desk, the ink, the paper), in order to build with the new spoils of catastrophe that keep growing all around us. The great challenge of political literature today is to create the wildest poetics with the rubbles of the dying worlds as a medium.